The PSOE’s Regeneration of International Socialism During the War in Spain - Lépine, Nicolas (Hispania Nova, 2024)
This article addresses the unknown transnational practices of the leading party of the Republican government during the civil war of 1936-39, the Partido Socialista Obrero Español (PSOE). Abandoned by liberal democracy and its international institutions, the PSOE broke diplomatic isolation by turning to its Labour and Socialist International (LSI) backchannel in an attempt to sway the policies of socialist parties, namely for the abrogation of non-intervention. Through this internationalist commitment, the PSOE revitalized a moribund network subjected to the appeasement and neutralist inclinations of its member sections. By shedding light on the PSOE’s transnational practice with the LSI and its French, Belgian, and British affiliates this article makes a contribution to the Spanish historiography on the internationalization/transnationalization of the conflict, while joining hands with Spanish historians using a more local lens. Moreover, and ultimately, it positions itself in the debate on whether labour history is internationally or nationally rooted.
Keywords: Spanish Civil War; Second Republic; International Socialism; internationalism; LSI; patriotism; interwar; PSOE; transnational solidarity